PENILAIAN TINGKAT KERUSAKAN JALAN DENGAN METODE SURFACE DISTRESS INDEX (Studi Kasus: Jl. Ploso Kerep dan Wukirsari) - Uray Ridho Ichsanul Rahman (Kampus Akademik Publiser, 2026)
The Ploso evacuation route is frequent - Wukirsari still causes problems for local residents to this day. The road track is uphill and the road condition is damaged, so you have to be careful when crossing the path. One of the factors causing the damage to the road is due to the passing of heavily loaded vehicles such as sand trucks that also often pass through the evacuation route. As a result, the road body was damaged because it was not in accordance with its intended purpose and had caused a traffic accident when passing through the road. The SDI method is used to visually assess damage Based on the SDI method, in 2025 Jalan Ploso Kerep Utara is in a Slightly Damaged condition with a percentage of 41% and good condition with a percentage of 59%. The condition of the South Ploso Kerep Road is in good condition with a percentage of 59%, a light damaged condition of 36%, and a heavy damage of 5%. On North Wukirsari Road 100% good condition, then South Wukirsari is in good condition 92% and medium 8%.